The Phoenician Name of Cyprus: New Evidence from Early Hellenistic Times. (15th February 2018) - Amadasi Guzzo, MG; Zamora, JA
Abstract: The Phoenician name of Cyprus was not known with certainty until now. From the beginning of the Iron Age to the Hellenistic period the island was divided into independent kingdoms, each kingdom named after its capital. For this reason, only the names of towns or regions appeared in local inscriptions of that period – not the name of the entire island, whose name in Phoenician was therefore unknown. In this paper, we intend to review the entire evidence relating to the question (from both the second and the first millennia BCE, both internal and external sources) and present a new document, definitively solving the problem.